2020
DOI: 10.1007/s10526-020-10041-y
|View full text |Cite
|
Sign up to set email alerts
|

Scrutinizing the enemy release hypothesis: population effects of parasitoids on Harmonia axyridis and local host coccinellids in Brazil

Abstract: The Enemy Release Hypothesis (ERH) has been a factor influencing the establishment of some exotic species worldwide. We tested if the ERH could be influencing populations of the exotic predator Harmonia axyridis (Pallas) (Coleoptera: Coccinellidae) in Brazil. During two years, three local predatory coccinellid species and Harmonia axyridis were sampled in Brassica oleracea in six organic farms in the midwest of the country. Parasitoids were detected by rearing (emerged) and qPCR Melting Curve Analysis (unemerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 40 publications
0
13
0
1
Order By: Relevance
“…Therefore, our study is the first report of low suitability in the field in South America and is confirmed by the results of laboratory tests. This, together with the results obtained in laboratory studies in Curitiba in Brazil (Castro-Guedes & Almeida, 2016), but not from field studies in the Distrito Federal in Brazil (Paula et al, 2020), indicate that at least two independent introductions of this invasive alien species to South America from eastern North America (Lombaert et al, 2014) have occurred, corresponding to populations that could better escape this natural enemy in comparison to other resident species (native or introduced). Therefore, even though the adaptation of natural enemies to novel invasive species is thought to occur by the ERH, in Chile, to date, D. coccinellae populations have not developed a strong ability to parasitize H. axyridis, contrary to what has occurred in some European populations that have had a longer period of interaction (Dindo et al, 2016;Knapp et al, 2019).…”
Section: Discussionmentioning
confidence: 79%
See 4 more Smart Citations
“…Therefore, our study is the first report of low suitability in the field in South America and is confirmed by the results of laboratory tests. This, together with the results obtained in laboratory studies in Curitiba in Brazil (Castro-Guedes & Almeida, 2016), but not from field studies in the Distrito Federal in Brazil (Paula et al, 2020), indicate that at least two independent introductions of this invasive alien species to South America from eastern North America (Lombaert et al, 2014) have occurred, corresponding to populations that could better escape this natural enemy in comparison to other resident species (native or introduced). Therefore, even though the adaptation of natural enemies to novel invasive species is thought to occur by the ERH, in Chile, to date, D. coccinellae populations have not developed a strong ability to parasitize H. axyridis, contrary to what has occurred in some European populations that have had a longer period of interaction (Dindo et al, 2016;Knapp et al, 2019).…”
Section: Discussionmentioning
confidence: 79%
“…Another possibility is that in the field, parasitoids attack larvae, which are less mobile and may be less aggressive than adults and therefore are less likely to escape from the parasitoid. In fact, studies have shown that even though adult coccinellids are the stage most attacked by D. coccinellae, fourth and third instar larval stages are also parasitized (Firlej, Boivin, Lucas, & Coderre, 2005;Obrycki et al, 1985;Paula et al, 2020). The fourth and third instar larvae of H. axyridis would also be more susceptible to parasitoid oviposition than adults, since they have less aggressive defensive behavior (Berkvens et al, 2010;Firlej et al, 2005Firlej et al, , 2010Hoogendoorn & Heimpel, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations